KONSEP PENDIDIKAN IBNU SINA TENTANG TUJUAN PENDIDIKAN, KURIKULUM, METODE PEMBELAJARAN DAN GURU - ., Musdalifah (Inspiratif Pendidikan, 2019)
Ibn Sina or Evicienna is one of the figures who has made a major contribution to the scientific realm, especially relating to Islamic education. Ibn Sina's thoughts about education were very structured. Starting from the objectives, curriculum, learning methods. According to Ibn Sina, teacher or educator are determinant elements in education. Ibn Sina's thoughts about Islamic education can be used as an important reference in advancing the world of education in Indonesia.